Effects of different depolymerisation methods on the physicochemical and antioxidant properties of polysaccharides derived from Sparassis latifolia. (November 2021) - Zhang, zuofa; Song, Tingting; Cai, Weiming; Wang, Fugen; Lv, Guoying
Graphical abstract: Highlights: Three depolymerised polysaccharides were prepared through different methods. The depolymerized SLPs exhibited higher antioxidant activity than the original SLP. HV-SLP possessed the highest antioxidant activity of the three depolymerised fractions. H2O2/Vc treatment is an effective method for preparing depolymerised SLP products. Abstract: Polysaccharides (SLP) derived from Sparassis latifolia were depolymerised by ultrasonication, hydrochloric acid, and H2 O2 /Vc to obtain the depolymerised polysaccharides U-SLP, H-SLP, and HV-SLP, respectively. Results from X-ray powder diffraction, atomic force microscopy, Fourier-transfrom infrared spectroscopy, proton nuclear magnetic resonance spectroscopy and scanning electron microscopy indicated that the SLP were damaged to varying degrees by the three methods. The results showed that the three depolymerisation methods broke down the molecular chains, impeded aggregation, and reduced the molecular weight of the polysaccharides without changing their primary structure and monosaccharide composition of SLP. Relative to the original SLP, the depolymerised SLPs showed higher antioxidant activity during in vitro ABTS and reducing power assays. Also, the depolymerised SLPs could effectively improve the survival rate of zebrafish and reduce their heart rate, reactive oxygen species production, and cell death. The HV-SLP had the highest antioxidant activity of the three depolymerised fractions. The results revealed that the H2 O2 /Vc treatment is an effective method for preparing depolymerised SLP products with low molecular weights and dramatic antioxidant activity.